An economic analysis of black pepper production in Malaysia using ARDL model / Ruhana Othman - Othman, Ruhana (Faculty of Plantation and Agrotechnology, 2018)
Pepper (Piper Nigrum L.) popularly known as King of spice is varied uses and dominance in the global spice trade, is the oldest and widely used spice in the world. Pepper has secured a pivotal position in food, pharmaceuticals, perfumery and cosmetic industries. Malaysia is the sixth largest pepper producer in the world. Black pepper has been a highly tradable commodity. The study determine the economic analysis black pepper production in Malaysia using annual data over period 1997-2016. The importance of this study comes from the necessity to determine important factors influencing of black pepper production in Malaysia. An Autoregressive Distributed Lag (ARDL) modelling is employed to investigate the impact of export of black pepper, price of black pepper and area planted of pepper on black pepper production. The findings of study illustrate that the ADF unit root test indicate that the export of black pepper, price of black pepper and area planted of pepper at first difference are stationary. The results of estimated long run coefficients using the ARDL approach for the export and price of black pepper positively significant with black pepper production. The Cumulative Sum of Recursive Residuals (CUSUM) were used to test for structural stability of the model. The ADRL bounds tests suggest that the independent variable series are co-integrated. The ECT also reveals that the independent variable have significant causative implications for black pepper production and able to readjust about 97.23% to long run equilibrium.